PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA PADA MATERI OPERASI BENTUK ALJABAR DI KELAS VII SMP NEGERI 2 TONDANO - Hanna Juwita Sembiring; Philotheus E. A Tuerah; Cori Pitoy (SOSCIED, 2025)
This study aims to determine whether there is an effect of applying the Snowball Throwing cooperative learning model on mathematics learning outcomes in grade VII on the subject of Algebraic Operations at SMP Negeri 2 Tondano using quantitative research through an experimental method with two classes randomly selected as subjects. The research instrument was a post-test consisting of multiple-choice and essay questions that had been tested for validity and reliability. From the hypothesis testing using the t-test, tcount = 5.567 > ttable = 2.023, which means rejecting Ho. Therefore, it can be concluded that the average learning outcomes of students on the subject of algebraic operations using the Snowball Throwing model are higher than the average learning outcomes of students using the conventional learning model.